COVID-19-Related Anxiety and the Coping Strategies in the Southeast Ethiopia - Teferu Engida, Zinash (Psychol Res Behav Manag, 2021)
BACKGROUND: The pandemic of coronavirus disease spreading is impacting mental health globally. Even though the pandemic is challenging for patients, the community, policymakers, as well as health organizations, and teams, the data on COVID-19 and its association with anxiety and coping mechanisms towards infection among community members are currently limited. Thus, the study is intended to assess COVID-19-related levels of anxiety and coping strategies among community members of Bale and East Bale Zones, Southeast Ethiopia. METHODS: A community-based survey was carried out among 634 study participants of Bale and East Bale Zones from June 1 to 20, 2020. The level of anxiety was determined by using the 5-item Coronavirus Scale and the coping strategies were determined by using the 15-item Coping and Adaptation Processing Scale. Interviewer-administered questionnaires were used to collect the data. Bi-variable analysis and multiple logistic regression analysis were used to estimate the relationship among the variables. RESULTS: COVID-19-related dysfunctional level of anxiety was found 95 (16.58%). About 290 (50.6%) respondents were copied from anxiety that occurred as a result of COVID-19. Factors significantly associated with the dysfunctional level of anxiety related to COVID-19 were being an urban resident (AOR = 0.44, 95% CI: 0.23, 0.86), those who had no information from TV/radio (AOR=1.76, 95% CI: 1.09, 2.84), and walking a long distance more than 1 hour from the health institution (AOR=0.58, 95% CI: 0.34, 0.97). CONCLUSION: COVID-19-related dysfunctional levels of anxiety were 16.58% in the study community. Half of the community was coped with COVID-19-related anxiety. Being an urban resident and walking along distances more than 1 hour from the health facility were the factors that decreased the odds of having a dysfunctional anxiety, whereas respondents who had no information from TV/radio increased the odds of having a dysfunctional anxiety. Accordingly, focusing on these identified factors could improve a dysfunctional level of anxiety in the study community.